Imaging Features of Hypertrophic Olivary Degeneration - Van Eetvelde, Ruth (J Belg Soc Radiol, 2016)
Hypertrophic olivary degeneration (HOD) is a unique form of transneuronal degeneration caused by a disruption of the dentato-rubro-olivary pathway, also known as the triangle of Guillain-Mollaret. The triangle of Guillain-Mollaret is involved in fine voluntary motor control and consists of both the inferior olivary nucleus and the red nucleus on one side and the contralateral dentate nucleus. Clinically, patients classically present with symptomatic palatal myoclonus. Typical magnetic resonance imaging findings include T2-hyperintensity and enlargement of the inferior olivary nucleus evolving over time to atrophy with residual T2-hyperintensity. In this article, we provide a case-based illustration of the anatomy of the Guillain-Mollaret-triangle and the typical imaging findings of hypertrophic olivary degeneration.